A Phenomenological Study of Gen Z Workers in Facing Conflict Generation Gap in the World of Work - I Putu Dharmawan Pradhana; Danny Bahari Kusnadhy; I Kadek Arya Wibawa Saputra; I Putu Yoga Purnama Wijaya; Andreas Pratama Sihaloho (Universitas Medan Area, 2024)
This research aims to determine the practical efforts that Generation Z can take to resolve or overcome the generation gap. The main challenge that an organization must face is how to manage and understand workers who come from various generations. Currently, there are several generations of work groups in an organization based on their age, such as that Gen Z workers often experience in Bali is the generation gap conflict. In this research, using qualitative methods with observation, interviews and documentation techniques, data was collected from 6 Generation Z people, 1 Generation Y person who works in the tour-ism sector, and one communications expert. Data analysis was conducted qualitatively with an interactive model and Nvivo 14 plus software. The validity of the data is checked through triangulation of sources and techniques. The research showed a mismatch in communication with their superiors and coworkers. However, they overcame it by implementing good communication patterns and adapting to their work environment. Thus, this research provides in-depth insight into the practical efforts made by Generation Z to resolve or overcome the generation gap.